Factors associated with time to first analgesic medication in the emergency department. Issue 13 (7th April 2021) - Hughes, James A.; Alexander, Kimberly E.; Spencer, Lyndall; Yates, Patsy
Abstract: Aim and Objective: To examine the factors associated with time to first analgesic medication in the emergency department. Background: Pain is the most common symptom presenting to the emergency department, and the time taken to deliver analgesic medication is a common outcome measure. Factors associated with time to first analgesic medication are likely to be multifaceted, but currently poorly described. Design: Retrospective cohort study. Methods: Cox proportional hazards regression modelling was undertaken to evaluate the associations between person, environment, health and illness variables within Symptom Management Theory and time to first analgesic medication in a sample of adult patients presenting with moderate‐to‐severe pain to an emergency department over twelve months. This study was completed in line with the STROBE statement. Results: 383 patients were included in the study, 290 (75.92%) of these patients received an analgesic medication in a median time of 45 minutes (interquartile range, 70 minutes). A model containing nine explanatory variables associated with time to first analgesic medication was identified. These nine variables (employment status, discharge location, triage score, Charlson score, arrival pain score, socio‐economic status, first location, daily total treatment time and patient time to be seen) represent all of the domains of the Symptom Management Theory. Conclusions: Person, environment, health and illness factors are associated with the time taken to deliver analgesic medication to those in pain in the emergency department. This study demonstrates the complexity of factors associated with pain care and the applicability of Symptom Management Theory to pain care in the emergency department. Relevance to Clinical Practice: Identifying a model of factors that are associated with the time in which the most common symptom presenting to the emergency department is treated allows for targeted interventions to groups likely to receive poor care and a framework for its evaluation.